Repercussions of COVID-19 on health personnel: Analysis from what was reported in the Colombian press - Arango Soler, Juan Manuel; Arango Soler, Luis Alfredo; Bernal Castro, Carol Andrea (Revista Española de Comunicación en Salud, 2022)
Introduction: Health personnel are among the groups that, due to their work, have the greatest chances of being infected with the SARS-CoV-2 virus, a human resource that has had to face different kinds of effects on their health, well-being, and quality of life. Objective: To reflect on the repercussions of COVID-19 on health workers in Colombia. Methodology: Descriptive study in which journalistic notes were explored on the web pages of the most representative press media in Colombia: El Tiempo.com, El Espectador newspaper and Revista Semana. The 80 selected articles were analyzed using an a priori category system. Results: The consequences for personnel are not exclusively evident in the fact of being infected or not by the virus, but in multiple spheres: mental health, violence and discrimination, family and social relationships, personal care activities, etc. Conclusion: The panorama of health workers in Colombia was complex before the occurrence of this international crisis. The pandemic has revealed those problems that had been brewing for many years.
Keywords: health personnel; coronavirus infections; communications media; Colombia